(untitled) (Proceedings of the European Wave and Tidal Energy Conference, 2023)
According to the European Council, 75% of the greenhouse emissions are caused by energy production and use. In order to decarbonize the energy sector, more research is focused towards the renewable energy sources. Among the many available resources, wave energy is one of the key resources to consider. As part of the research, KTH is developing a winch based point absorber wave energy converter. The winch consists of a chain link with elastomer bearings wound around a drum. The winding and unwinding motion of chain converts wave motion into electricity. A typical winch based wave energy converter undergoes around 80 million cycles in its lifetime. This calls for a durable system design requiring minimal service and maintenance. With an elastomer bearing, the winding and unwinding of the chain over the drum is realized as deformation of the elastomer thereby eliminating sliding. While the use of elastomer enables an efficient design, it also makes it more challenging due to its highly non-linear and viscoelastic behavior. A constitutive model is necessary to determine material characteristics of an elastomer for different loading conditions. In this work, a systematic design process is outlined and an attempt is made to determine a suitable hyperelastic material model for the elastomer. The study is focused on two materials – silicone and polyurethane. The test samples are compressed and followed by shear in deformation. For material model determination, the test data is curve fit and later verified using finite element method. The material is assumed incompressible.